Pengaruh Kompensasi, Gaya Kepemimpinan, dan Motivasi Kerja terhadap Kinerja Karyawan di PT Berdikari Putra Abadi Cabang Kota Semarang - Nadia Putri Rahmadita; Fahrur Rozi (Jurnal Ragam Pengabdian, 2026)
This study was conducted to examine the influence of compensation, leadership style, and work motivation on employee performance at PT Berdikari Putra Abadi Semarang Branch. The research was motivated by a continuous decline in sales performance during the period 2021–2025, reflected in a 41.7% decrease in distribution quantity and a 42.1% decline in sales revenue. A quantitative approach with a causal associative design was employed. The study involved all 41 employees using a saturated sampling technique. Data were collected through questionnaires and company Key Performance Indicator (KPI) records and analyzed using multiple linear regression with SPSS. The findings indicate that compensation and leadership style have a positive and significant effect on employee performance, with leadership style emerging as the strongest predictor. Work motivation also has a significant effect but demonstrates a negative relationship with performance. Simultaneously, the three independent variables explain 47.1% of the variance in employee performance, while the remaining 52.9% is influenced by other factors outside the research model. The study concludes that improving employee performance requires not only fair compensation but also effective leadership and appropriate management of employee motivation.